Economic assessment of Power-to-Liquid processes – Influence of electrolysis technology and operating conditions. (15th June 2021) - Herz, Gregor; Rix, Christopher; Jacobasch, Eric; Müller, Nils; Reichelt, Erik; Jahn, Matthias; Michaelis, Alexander
Highlights: NPC of syncrude derived from H2 O and CO2 were calculated for 2020 and 2050. PEM- and SOEL-based PtL concepts were compared. For 2020, the NPC of the PEM-based process is lower due to lower equipment cost. For 2050, SOEL allows for lower NPC due to higher efficiency. Abstract: Power-to-Liquid (PtL) processes are considered as a key technology for a fossil-free raw material and energy system. With multiple technical analyses being available and technical feasibility being proven by first pilot plants, pathways towards commercial market entry are of increasing interest. In this work multiple economic aspects of Power-to-Liquid plants are being investigated. First and foremost, the seamless integration of an economic analysis in the process modeling workflow will be demonstrated. This allows for an extensive investigation of the influence of operating conditions of the considered solid oxide electrolyzer (SOEL) on process economics and a subsequent optimization not only from an engineering standpoint but considering economics as well. Furthermore, the modular nature of the model allows for a comparison of SOEL to the more mature technology of low-temperature electrolysis with a focus on possible heat integration and by-product utilization. The potential of SOEL technology for high energetic efficiency and subsequently low production cost is highlighted. The conducted forecast to 2050 shows that SOEL-based Power-to-Liquid processes offer lower production cost of NPC = 0.203 €2020 /kWhch compared to production cost of NPC = 0.262 €2020 /kWhch for the PEMEL-based process. Furthermore, based on the results of the economic assessment possible governmental support mechanisms are studied, showing that projected values for governmental incentives are expected to decrease CO2 mitigation cost from κCO2 = 791 €2020 /tCO2 to κCO2 = 419 €2020 /tCO2 for the 2050 scenario. Thus, existing measures and currently discussed measures are not sufficient to ensure economic viability. Consequently, more extensive schemes such as mandatory quotas for sustainable PtL products need to be implemented in order to facilitate the market entry.